Ovarian Hyperstimulation Syndrome and Myocardial Infarction: A Systematic Review - Mohammed Al-Sadawi; Richi Chowdhury; Seline Asun; Justina Ray; Lina Soni1; Gul Bahtiyar; Debora Ponse; Samy I McFarlane (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2019)
Background: Ovarian hyperstimulation syndrome (OHSS) is a rare but serious complication of ovarian stimulation occurring during assisted reproduction technologies (ART). It is characterized by increased vascular permeability and hypercoagulable states resulting in strokes and peripheral ischemia. Acute myocardial infarction and cardiac thrombosis, however, have been rarely reported complications of OHSS.  Methods: A literature search was performed for reports on myocardial infarction and cardiac thrombosis associated with ovarian stimulation with a summary of their clinical characteristics.  Results: A total of twelve published cases were reviewed with 5 out of 12 (41.67%) of the reported cases were 35 years of age or older. Myocardial infarction was reported in 10 out of the 12 cases (83.3%). Two of the cases were pregnant at presentation (16.67%). The mean duration between starting ovarian stimulation medications and clinical presentation was 23 days. Chest pain was the most common presenting symptom (66.67%), 2 cases presented with stroke (16.67%) and 2 cases presented with abdominal distention (16.67%). A total of 8 patients underwent coronary angiography with 2 of these cases were treated with percutaneous coronary intervention. No mortality reported in any of the twelve cases.  Conclusion: Women of a relatively younger age undergoing ovarian stimulation may be at risk for developing myocardial infarction and cardiac thrombosis. Once thrombosis is suspected, initiating appropriate therapy in a timely manner is crucial.